2021
DOI: 10.3390/nu13041228
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Metabolic Impact of Mediterranean Diet in Type 2 Diabetes: Is Gut Microbiota the Key?

Abstract: The Mediterranean diet (MD) has been recommended for type 2 diabetes (T2D) treatment. The impact of diet in shaping the gut microbiota is well known, particularly for MD. However, the link between MD and diabetes outcome improvement is not completely clear. This study aims to evaluate the role of microbiota modulation by a nonpharmacological intervention in patients with T2D. In this 12-week single-arm pilot study, nine participants received individual nutritional counseling sessions promoting MD. Gut microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…Although both Roseburia and Lachnospira increased at one month, only Pseudomonas increased significantly after six months. In a 12-week uncontrolled pilot study, Ismael et al also studied a Mediterranean-based diet in T2DM patients and showed a decrease in both FBG (131.63 ± 8.53 vs. 122.50 ± 9.42 mg/dL, p = 0.581) and HbA1c (7.53 ± 1.07 vs. 6.86 ± 0.85%, p = 0.025) [ 72 ]. There was also a trend towards an increase in alpha diversity ( p = 0.47) and relative abundances of Bacteroides , Ruminococcus , Akkermansia , and Roseburia , while the relative abundance of Faecalibacterium and Prevotella decreased.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although both Roseburia and Lachnospira increased at one month, only Pseudomonas increased significantly after six months. In a 12-week uncontrolled pilot study, Ismael et al also studied a Mediterranean-based diet in T2DM patients and showed a decrease in both FBG (131.63 ± 8.53 vs. 122.50 ± 9.42 mg/dL, p = 0.581) and HbA1c (7.53 ± 1.07 vs. 6.86 ± 0.85%, p = 0.025) [ 72 ]. There was also a trend towards an increase in alpha diversity ( p = 0.47) and relative abundances of Bacteroides , Ruminococcus , Akkermansia , and Roseburia , while the relative abundance of Faecalibacterium and Prevotella decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Pedersen et al showed significant positive associations between unclassified Enterobacteriaceae (Proteobacteria phylum) and FBG and hs-CRP ( p < 0.05) after fiber supplementation [ 73 ]. Additionally, negative correlations were found between alpha diversity (Shannon index) and B. longum with HbA1c after high-fiber dietary interventions (rs = −0.458, p < 0.05 and p < 0.01, respectively) [ 70 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 67 Table 1 summarizes studies with statistically significant differences in the composition after dietary intervention for T2D patients. 68–70 Furthermore, the differences in clinical parameters are closely related to changes at various levels of taxa (phylum, family, genus, species, and Firmicutes: Bacteroidetes relationship) ( Table 1 and Table S3).…”
Section: Factors That Modulate the Microbiome In Patients With T2dmentioning
confidence: 99%
“…However, the diversity and abundance of healthy gut microbiota can be disrupted by factors, leading to gut dysbiosis which can involve pathobiont proliferation and depletion of commensal bacteria [11]. These gut microbiota alterations have been associated with several diseases including diabetes, asthma, colorectal cancer and Parkinson's disease [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%